2018
DOI: 10.1111/sji.12674
|View full text |Cite
|
Sign up to set email alerts
|

The role of Th1/Th2 cytokines played in regulation of specific CD4 + Th1 cell conversion and activation during inflammatory reaction of chronic obstructive pulmonary disease

Abstract: CD4 Th1-CXCR3 signalling pathway may play a key role in chronic obstructive pulmonary disease (COPD). The aim of this study was to explore Th1/Th2 cytokines ratio differences in patients in different stages of COPD and to confirm the hypothesis that elastin exposure might serve as an antigen to initiate the stimulation of CD4 Th1-CXCR3 immune inflammation pathway. Patients of COPD in different stages and normal individuals were enrolled. Ten millilitres of peripheral blood was drawn from patients. The concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
(37 reference statements)
3
18
0
Order By: Relevance
“…Normally, Th1/Th2 cells are in a relatively balanced state under normal conditions. However, studies have shown that there are imbalances of Th1/Th2 in different periods of COPD [10, 31]. In this study, we found that Th1 cells gradually increased in stable phase of COPD and AECOPD, and the expression of IFN- γ also showed the same trend.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Normally, Th1/Th2 cells are in a relatively balanced state under normal conditions. However, studies have shown that there are imbalances of Th1/Th2 in different periods of COPD [10, 31]. In this study, we found that Th1 cells gradually increased in stable phase of COPD and AECOPD, and the expression of IFN- γ also showed the same trend.…”
Section: Discussionsupporting
confidence: 62%
“…Lower respiratory tract bacterial infection is an important factor in the occurrence of AECOPD, which can lead to immune dysfunction. Studies also found that the abnormality of T cell subsets is the main cause of immune dysfunction in COPD [79] and Th1/Th2 imbalance may be one of the causes of AECOPD [10]. It is reported that the activation and proliferation of Th2 cells in the peripheral blood of patients with AECOPD were more obvious, resulting in a significant downregulation of Th1/Th2 ratio and a shift to Th2 responses [11].…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary infection may directly affect lung function and the prognosis of patients with COPD. WBCs, 11 CRP, 21 IL-6, 13 IL-8 14 and TNF-α 15 are associated with inflammatory cells and the alveolar epithelium in patients with COPD; these factors are closely related to the level of infection, lung function, and severity of illness. Higher levels of inflammatory indicators in the blood are associated with more severe infection and more serious lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that in COPD patients with acute exacerbation the level of Th1 was reduced whereas the level of Th2 was predominant. Oppositely, Th2 cells have been shown to decrease in stable COPD patients while Th1 cells increased [31]. In our study, using an IFN-γ-expressing CD4 + T-cells percentage of < 12% as threshold, we identified and selected two distinct groups of patients: (i) a first group of patients with more than 40% of CD4 + T-cells expressing IL-4 (IL-4 high IFN-γ low ) and (ii) a second group with less of 20% of CD4 + T-cells expressing IL-4 (IL-4 low IFN-γ low ).…”
Section: Controlsmentioning
confidence: 99%